2010
DOI: 10.1007/s00423-010-0709-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of infectious complications after laparoscopic appendectomy for complicated acute appendicitis—the role of routine abdominal drainage

Abstract: No benefits were observed for prophylactic drainage of the abdominal cavity during emergency laparoscopic treatment of complicated appendicitis. For this reason, this practice may be abandoned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 32 publications
4
45
0
2
Order By: Relevance
“…These results are consistent with recent retrospective studies [1,3,7,8,10,14], and, therefore, LA for CA is considered safe and feasible with improvements in techniques and devices. Nonetheless, the roles of extensive irrigation and routine drainage to reduce risks of IAA that were employed in this study remain debatable [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with recent retrospective studies [1,3,7,8,10,14], and, therefore, LA for CA is considered safe and feasible with improvements in techniques and devices. Nonetheless, the roles of extensive irrigation and routine drainage to reduce risks of IAA that were employed in this study remain debatable [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not show the relationship of peritoneal drainage with peritoneal irrigation, while we could further demonstrate how peritoneal drainage would be beneficial when it is consequently applied after peritoneal irrigation. A recent metaanalysis reported that neither simple nor a gangrenous nor a perforated appendicitis benefit from the routine use of prophylactic drainage and that, furthermore, drainage did not reduce postoperative complications [23][24][25] . In addition, the use of routine drainage in contaminated and infected abdominal surgery is declining [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Die Indikationsstellung zur Drainageneinlage sollte jedoch befundabhängig erfolgen. Beispielsweise scheint eine systematische Drainageneinlage bei der perforierten Appendizitis nachteilig zu sein [2]. Falls nach gründlicher Lavage eine makroskopische Verschmutzung verbleibt, können zusätz-lich Spüldrainagen zur kontinuierlichen postoperativen Lavage platziert werden.…”
Section: Prävention Persistierende/ Rezidivierende Entzündungunclassified